Recursos educativos digitais e o ensino/aprendizagem da gramática - Cardoso, Adriana; Rodrigues, Ricardo Pereira; Freitas, Liliana; Alves, Dina Caetano (Revista da Associação Portuguesa de Linguística, 2020)
This paper presents two digital educational resources (DER), which aim at promoting the development of metalinguistic competence of students attending the 3rd grade of Primary School (age 8/9). The digital resource Laboratório Gramatical Digital: A Força das Sílabas [Digital Grammar Lab: The strength of syllables] promotes the development of metaphonological competence of students on the phonological word stress in European Portuguese. It adopts a discovery-learning approach through the implementation of a grammar laboratory (‘Grammar Lab’). The digital resource Cozinhar a Aprender [Cooking to Learn] offers a learning experience where users build their own knowledge on a specific textual genre (recipe) through the analysis of concrete examples (or models) of this textual genre. The didactic approach implemented draws upon the notion of text genre and the model of didactic sequence. These two DER aim to contribute to a paradigm shift from traditional practices towards more active and student-centered ones.